(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article deals with titles’ specification in the texts of European Ovidiana of the second half of the 20th century. The problem is relatively fresh in literary criticism and needs a new study. On the basis of comparative typological approach the implicit meaning of headings «Naso the Poet» by Jacek Bochenski, «The Last World» by Christoph Ransmayr, «Scandal in the Emperor’s Family» by Valentin Chemeris and «The Summer Swam on the Winter Shore» by Juriy Mushketyk has been exposed. The expansion of literary sources allowed the researcher to reasonably prove the title’s determination as a key to a first presentative interpretation of the text.